Tuberculosis Care in Mexico's Chiapas Highlands Region: A Right to Health Analysis - Andrea Pérez-Molina; Héctor Javier Sánchez-Pérez; Maritel Yanes-Pérez; Marcos Arana-Cedeño (Harvard FXB Center for Health and Human Rights, 2020)
This article analyzes the fulfillment of the four essential and interrelated elements of availability, accessibility, acceptability, and quality (AAAQ) presented in General Comment 14 of the United Nations Committee on Economic, Social and Cultural Rights. We examined the ways that AAAQ criteria are met in tuberculosis (TB) care by evaluating a sample of 33 primary health care units (PHCUs) in 10 municipalities of the Chiapas Highlands region of Mexico. We collected information about 56 people with TB who were treated in those PHCUs, the structural conditions of the health facilities, and data about all health care workers in the PHCUs (n=423). Our results show that there is great variability in how AAAQ criteria are met among the PHCUs and in the way that TB care programs are delivered. Resource shortages and infrastructure characteristics hinder the fulfillment of AAAQ elements despite the commitment made by Mexico to guarantee the right to health as outlined in General Comment 14.